1999
DOI: 10.1177/0730888499026001006
|View full text |Cite
|
Sign up to set email alerts
|

Whistle-Blower Disclosures and Management Retaliation

Abstract: Based on nationwide data the authors collected on whistle-blowers and on silent observers, this article reports, that (a) whistle-blowing is more frequent in the public sector than in the private; (b) there are almost no sociodemographic characteristics that distinguish the whistle-blower from the silent observer; (c) whistle-blowers suffer severe retaliation from management, especially when their information proves significant; and (d) no special method of disclosure or personal characteristics can insulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
132
1
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(147 citation statements)
references
References 9 publications
2
132
1
12
Order By: Relevance
“…Dibutuhkan keberanian dan keyakinan untuk melakukannya sehingga beberapa whistleblower menerima pujian heroik (Johnson, 2003). Dimana sebagian orang memandang whistleblower sebagai pengkhianat yang melanggar norma loyalitas organisasi, sebagian lainnya memandang whistleblower sebagai pelindung heroik terhadap nilai-nilai yang dianggap lebih penting dari loyalitas kepada organisasi (Rothschild dan Miethe, 1999). Selain itu, whistleblower dapat membantu organisasi memperbaiki produk yang tidak aman atau menyediakan sumber informasi penting dalam mempertahankan kinerja organisasi yang kompleks (Miceli dan Near, 1985).…”
Section: Pendahuluanunclassified
“…Dibutuhkan keberanian dan keyakinan untuk melakukannya sehingga beberapa whistleblower menerima pujian heroik (Johnson, 2003). Dimana sebagian orang memandang whistleblower sebagai pengkhianat yang melanggar norma loyalitas organisasi, sebagian lainnya memandang whistleblower sebagai pelindung heroik terhadap nilai-nilai yang dianggap lebih penting dari loyalitas kepada organisasi (Rothschild dan Miethe, 1999). Selain itu, whistleblower dapat membantu organisasi memperbaiki produk yang tidak aman atau menyediakan sumber informasi penting dalam mempertahankan kinerja organisasi yang kompleks (Miceli dan Near, 1985).…”
Section: Pendahuluanunclassified
“…Further, research by Rothschild and Miethe (1999) reported that displays of moral courage in the form of whistle blowing were not sufficiently explained by individual differences and that one would also have to examine situational determinants to explain these actions. We propose leadership is one such critical determinant.…”
Section: Authentic Leadership and Follower Moral Courage And Behaviormentioning
confidence: 99%
“…External whistleblowing can then be defined as reporting wrongdoing to someone outside the organization who may be able to stop or correct it. Most external whistleblowers first blow the whistle internally (Miceli et al, 2008;Rothschild & Miethe, 1999) as the latter is less risky for the whistleblower (Miceli & Near, 2002) and also less detrimental to the organization (Hassink et al, 2007). In contrast, external whistleblowing may lead to public embarrassment, government scrutiny, hefty fines, and litigation (Berry, 2004) as it not only exposes internal wrongdoing, but also a failing organization -one which is unable to stop and correct wrongdoing itself.…”
Section: Hypotheses Responses To Observed Wrongdoingmentioning
confidence: 99%
“…(Berry, 2004), or "Do I snitch or do I not snitch" (Pershing, 2003). When employees refrain from taking action, they become "inactive observers" (Miceli & Near, 1992) or "silent observers" (Rothschild & Miethe, 1999), which is undesirable when the norm is to prevent, detect and correct wrongdoing (Miceli et al, 2008). 1 When employees decide to take action, different options are available (cf., Elliston, 1982;Hirschman, 1970;Jubb, 1999;Miceli & Near, 1984).…”
Section: Hypotheses Responses To Observed Wrongdoingmentioning
confidence: 99%